PEMBELAJARAN PENGETAHUAN LINGKUNGAN MENGGUNAKAN METODE PEMECAHAN MASALAH ATAU PROBLEM SOLVING UNTUK MAHASISWA TPB DI JURUSAN PENDIDIKAN BIOLOGI - Syulasmi, Ammi; Sihombing, Pariama; Amprasto, Mr; Fitriani, Any (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2001)
The result of evaluation on Environmental Science for student of Biology education was still low. The average result obtained from the last 3 years were A = 7,63 %; B = 29,11%; C = 52,83 %; D = 7,11 % and E = 2,25 %. It indicated that the learning process of this subject was not effective enough. Therefore, it has to be though, how to conduct this teaching learning process of Environmental Science learning effectively. Environmental Science is an interdisciplinary science. It allows the student to think in a holistic way. Therefore in this study, problem-solving method is appropriate to apply in this learning process. In the method students were trained how to solve the environmental problem which involving some sciences. Further more along with the development of Environmental Science, it can allow the students to find out information in order to solve the environmental problems. In this learning process of Environmental Science, students have lectures, practical exercises and field works. In the fieldwork, students have to define the environmental problem and how to solve the problem. This fieldwork is supported by field observation, group discussion and paper presentation. In this method, the result is increasing. It can be shown with the student who have: A = 26,66 %; B = 53,33 %; C = 18,33 %; D = 5,0 % and E = 0 %. Keywords: Environmental Science, Problem Solving, and Fieldwork.